Interaction of environmental factors and physical exercise in the development of amyotrophic lateral sclerosis and the potential of pharmacology and targeted therapies - a Narrative Review - Zięba, Natalia; Czapiński, Olgierd; Brodowska, Anna; Knapik, Anna; Białowąs, Patrycja; Pysiewicz, Mateusz; Kuś, Justyna; Ciesielski, Maciej; Tomicka, Ewa; Stadnicka , Olga; Czech, Mateusz (Quality in Sport, 2026)
Background: Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disease leading to motor neuron degeneration and muscle atrophy. Its etiology remains unclear, although environmental and lifestyle factors may contribute to disease development. Aim: This review analyzed the influence of environmental factors and physical activity on ALS risk, as well as current and emerging treatment strategies. Material and methods: Articles published between 2017 and 2026 were reviewed using PubMed, GeneReviews, StatPearls, and Google Scholar databases. Original studies and review papers concerning ALS risk factors and therapies were included. Results: Exposure to chlorinated pesticides, cadmium, lead, tobacco smoke, and cigarette smoking was associated with increased ALS risk. Studies on air pollution produced inconclusive findings. A higher ALS incidence was observed among NFL players, although the direct role of physical activity remains uncertain. Some large population studies suggested that regular physical activity may lower ALS risk. Despite available disease-modifying therapies, ALS remains incurable. Conclusions: Exposure to pesticides and toxic metals may increase ALS risk and should be minimized. Evidence regarding physical activity and ALS is inconsistent and requires further research. Continued development of therapies targeting ALS pathogenesis is necessary.